Reduced oligodendrocyte exosome secretion in multiple system atrophy involves SNARE dysfunction - Yu, Zhenwei; Shi, Min; Stewart, Tessandra; Fernagut, Pierre-Olivier; Huang, Yang; Tian, Chen; Dehay, Benjamin; Atik, Anzari; Yang, Dishun; De Giorgi, Francesca; Ichas, François; Canron, Marie-Hélène; et al. (Brain (London, England : 1878), 2020)
Transportation of key proteins via extracellular vesicles has been recently implicated in various neurodegenerative disorders, including Parkinson’s disease, as a new mechanism of disease spreading and a new source of biomarkers. Extracellular vesicles likely to be derived from the brain can be isolated from peripheral blood and have been reported to contain higher levels of α-synuclein (α-syn) in Parkinson’s disease patients. However, very little is known about extracellular vesicles in multiple system atrophy, a disease that, like Parkinson’s disease, involves pathological α-syn aggregation, though the process is centred around oligodendrocytes in multiple system atrophy. In this study, a novel immunocapture technology was developed to isolate blood CNPase-positive, oligodendrocyte-derived enriched microvesicles (OEMVs), followed by fluorescent nanoparticle tracking analysis and assessment of α-syn levels contained within the OEMVs. The results demonstrated that the concentrations of OEMVs were significantly lower in multiple system atrophy patients, compared to Parkinson’s disease patients and healthy control subjects. It is also noted that the population of OEMVs involved was mainly in the size range closer to that of exosomes, and that the average α-syn concentrations (per vesicle) contained in these OEMVs were not significantly different among the three groups. The phenomenon of reduced OEMVs was again observed in a transgenic mouse model of multiple system atrophy and in primary oligodendrocyte cultures, and the mechanism involved was likely related, at least in part, to an α-syn-mediated interference in the interaction between syntaxin 4 and VAMP2, leading to the dysfunction of the SNARE complex. These results suggest that reduced OEMVs could be an important mechanism related to pathological α-syn aggregation in oligodendrocytes, and the OEMVs found in peripheral blood could be further explored for their potential as multiple system atrophy biomarkers.